Gidon Kremer : Kremerata Baltica. - Hohlfeld, Horant H.; Kandinskai︠a︡, Anna; Kremer, Gidon, 1947-; Nemanyte, Marija; Pushkarev, Andrei; Rubinas, Danielis; Sudraba, Marta; Tepp, Reinut; Ulijona, Ula; Bor, Teddy; Mozart, Wolfgang Amadeus, 1756-1791.; Mozart, Wolfgang Amadeus, 1756-1791.; et al. ([Leipzig] : EuroArts, 2002)
Gidon Kremer is one of the world's foremost violinists and -- thanks to his insatiable curiosity and quest for new stimuli -- one of today's most intriguing musical personalities. In 1997 he gave himself a special present for his fiftieth birthday -- his own ensemble, made up of the best young musicians from the Baltic countries, the Kremerata Baltica. "For me it's extremely important that I and my Kremerata Baltica identify with the music of our time." This is an example of his uncommonly extensive repertoire, featuring some of the greatest pieces ever composed -- from Bach to the new world of thrilling 20th century works.
Sinfonia concertante for violin, viola and orchestra, K364 (320d) ; Serenade in D major, K329 : Serenata notturna / Wolfgang Amadeus Mozart -- McMozart's Eine kleine bricht Moonlicht nicht Musik / Teddy Bor -- Mozart-Adagio / Arvo Pärt -- Moz-Art à la Haydn / Alfred Schnittke.
Kremerata Baltica: Gidon Kremer, Marta Sudraba (violoncello) ; Anna Kandinskaja, Marija Nemanyte (violin) ; Ula Ulijona (viola) ; Danielis Rubinas (double bass) ; Reinut Tepp (piano) ; Andrey Pushkarev (percussion).
Keywords: Concert films; Piano trios; String orchestra music; Suites (Violins (2), viola, double bass with string orchestra); Violin and viola with chamber orchestra; Violins (2) with string orchestra; Concerts filmés.; Trios pour piano; Orchestre à cordes, Musique d'.; Violon, alto et orchestre de chambre; Violons (2) et orchestre à cordes; Concert films; Piano trios; String orchestra music; Suites (Violins (2), viola, double bass with string orchestra); Violin and viola with chamber orchestra; Violins (2) with string orchestra; Streaming videos; Nonfiction films; Nonfiction films; Films autres que de fiction